APPLICATION OF THE PROBLEM POSING MODEL TO IMPROVE THE ABILITY OF FIFTH GRADE STUDENTS TO SOLVE MATHEMATICAL STORY PROBLEMS AT THE UPT SPF SD INPRES KARUNRUNG, MAKASSAR CITY: Makasar, Indonesia - Azizah, Nurul; Patta, Rahmawati; Riang Tati, Andi Dewi (Universitas Muhammadiyah Bengkulu, 2025)
This study originated from the lack of involvement of fifth-grade students in learning and their low ability to solve mathematical story problems, which did not meet the Learning Objective Criteria (KKTP). To address this issue, this study aims to examine the improvement of mathematics learning through the application of the Problem Posing model. Using the Classroom Action Research (CAR) method with a qualitative approach, this study was conducted in two cycles. Each cycle included planning, implementation, observation, and reflection. The research subjects were teachers and 25 fifth-grade students at UPT SPF SD Inpres Karunrung (7 male students and 18 female students). In Cycle I, observations showed that the learning process (both from the teacher and student perspectives) and learning outcomes were at a satisfactory level. After improvements were implemented, Cycle II showed a significant improvement, with all aspects of the learning process from the teacher's side, the learning process from the students' side, and learning outcomes improving to a good level. The conclusion of this study is that the Problem Posing model is a successful approach in improving the ability of fifth-grade students at UPT SPF SD Inpres Karunrung in Makassar City to solve math story problems. Keywords: Problem Posing Model, Ability to solve story problems